Fatty acid composition of abdominal adipose tissue in broilers fed green-oak (Quercus ilex), cork oak acorn (Quercus Suber L.) based diets - Bouderoua, Kaddour; SELSELET-ATTOU, Ghalem (Anim. Res., 2003)
Male broilers, 30 for every diet, were fed for six weeks, diets containing 60% green oak (GO) and oak cork (CO) acorns compared to 60% corn (C). The body weight of the chickens fed the oak acorn-based diets was 25% lower than that of the controls (C). Abdominal adipose tissue (AAT) was twice heavier in the controls compared to broilers fed oak acorn-based diets. The total lipids of AAT were higher in the controls compared to the oak acorn fed chickens (34.4 against 15.3 g per 100 g of AAT in the CO). The palmitic and oleic acid proportions were comparable in the AAT of chickens fed with the different diets. The proportion of linoleic acid, obtained exclusively by the diets, was significantly higher in the chickens fed oak acorn-based diets (23%), compared to the controls (19%). Reciprocally, palmitoleic acid was present in a small proportion in chickens fed oak acorns (4 to 5%). The observed variation of the fatty acid content of abdominal fat of acorn-fed chickens requires further research on the precise nutrient digestibility of oak acorns before considering them as a potential feed.
Keywords: lipids / lipogenesis / broilers / oak acorn / adipose tissue.